Effect of coherent jet burner on scrap melting in electric arc furnace. (25th July 2022) - Chen, Yuchao; Luo, Qingxuan; Ryan, Steve; Busa, Neel; Silaen, Armin K.; Zhou, Chenn Q.
Highlights: First proposed an integrated CFD model for scrap melting by coherent jet burner. First designed and conducted experiments in an industrial EAF for model validation. Applied model to explore impacts of burner/scrap conditions on energy utilization. Provided an understanding for more effective scrap melting in EAF. Abstract: Modern electric arc furnace (EAF) steelmaking relies on the coherent jet burner to melt scrap at the cold spots inside the furnace, but the relevant computational fluid dynamics (CFD) modeling of this process has not been reported and systematically studied. The present work established an innovative comprehensive CFD model including a scrap melting model and a coherent jet model based on the detailed physical principles, which couples the solid–liquid-gas three-phase system with coherent jet and scrap melting/re-solidification for the investigations of key evaluation factors including burner efficiency, scrap heating rate, and scrap melting cavity. An experiment was designed and implemented specifically in an industrial-scale EAF for validating the proposed model. The model was employed to explore the impacts of burner power, scrap porosity, scrap preheat temperature, and scrap blockage on burner energy utilization. An understanding and guidance of coherent jet burner operations were provided based on the studies for more effective scrap melting.